Successive Oral Immunizations Against Piscirickettsia Salmonis and Infectious Salmon Anemia Virus are Required to Maintain a Long-Term Protection in Farmed Salmonids - Tobar, Iván; Arancibia, Sergio; Torres, Constanza; Vera, Verónica; Soto, Paola; Carrasco, Claudia; Alvarado, Marcelo; Neira, Eduardo; Arcos, Sandra; Tobar, Jaime A. (Frontiers in Immunology, 2015)
Currently, there is a growing demand to determine the protective status of vaccinated fish in order to prevent diseases outbreaks. A set of different parameters that include the infectious and immunological status of vaccinated salmonids from 622 Chilean farms were analyzed during 2011-2014. The aim of this study was to optimize the vaccination program of these centers through the determination of the protective state of vaccinated fish using oral immunizations. This state was measured by the association of the concentration of the immunoglobulin M (IgM) in the serum and the mortality rate of vaccinated fish. Salmonids were vaccinated with different commercial mono- or polyvalent vaccines against SRS and ISAv, first by the intraperitoneal injection of oil-adjuvanted antigens and then by the stimulation of mucosal immunity using oral vaccines as booster. The results showed that high levels of specific IgM antibodies were observed after injectable vaccination, reaching a maximum concentration at 600-800 degree-days. Similar levels of antibodies were observed when oral immunizations were administrated. The high concentration of antibodies (above 2750 ng/mL for ISAv and 3500 ng/mL for SRS) was maintained for a period of 800 degree-days after each vaccination procedure. In this regard, oral immunizations maintained a long-term high concentration of anti-SRS and anti-ISAv specific IgM antibodies. When the concentration of antibodies decreased below 2000 pg/mL, a window of susceptibility to SRS infection was observed in the farm, suggesting the close association between antibody levels and fish protective status. These results demonstrated that, in the field, several oral immunizations are essential to uphold a high level of specific anti-pathogens antibodies and, therefore, a protective status during the whole productive cycle.